TECHNICAL CAPACITY NEW ARTISTIC PROCESSES AS A CREATION TOOL - Otajon O‘ktamovich Dostonov (Journals Park Publishing, 2022)
This scientific article Uzbek cinematographer taught lullanilayetgan technician shanslar, Yang badiy zharaennish yaratish-a qualitative tool for the study of atlich. Katta avlad deputy H. Khasanov, deputy U. Malikov portrays Olgan on film the episode analyzes the frame of the series, portrays Olga technikalari, style operator, yoroglik oracle Badi hasanilgan.
Keywords: creativity, artistry, a staff, a young operator, a school of cinematography